SCIENTIFIC AND METHODOLOGICAL SUPPORT FOR WILDLIFE FORENSICS: CURRENT STATE AND DEVELOPMENT PERSPECTIVES - V. Gulevskaya (Теория и практика судебной экспертизы)
The paper highlights the current state and key trends in the development of the scientific and methodological support for the forensic investigation of crimes against wild flora and fauna, and argues for a need to develop specialized methodological materials for wildlife forensics practitioners in the form of standard operational procedures.